A study on the prevalence, behavioural patterns, and risk factors of vitamin D deficiency in the population of southern Saudi Arabia - Zahrani, Yousef; Zeyaullah, Md.; Khan, Mohammad Suhail; Ahmad, S Rehan; AlShahrani, Abdullah M.; Ahmad, Ausaf; Mohieldin, Ali; Mahmood, Syed Esam; Riaz, Fatima; Alraee, Nouf Abdullah; Muzammil, Khursheed; Narapureddy, Bayapa Reddy; et al. (Progress in Nutrition, 2024)
Introduction: This deficiency is one of the most common nutritional deficiencies now considered a public health problem in developed and underdeveloped countries. Aim: This study aims to identify the general people in the Aseer region of southern Saudi Arabia's Awareness of vitamin D deficiency, their behaviour patterns, and their knowledge of risk factors. Methodology: This cross-sectional community study was conducted in two cities of the Aseer Region, Abha and Khamis Mushayt. By applying a Simple random sampling technique, four Malls were selected, and two malls were in each city. The sample size was calculated by taking the prevalence from the previous study and putting on the formula 4Pq/D2. Eight hundred eighty respondents participated in the study. Multiple logistic regression and chi-square tests were used to analyse the significance and relationships between the variables. Results: Most participants knew about vitamin D insufficiency and its associated risk factors. Approximately 87.95% of respondents knew the need for vitamin D for health, and 86.82% had heard of vitamin D deficiency. 94.09% of the participants were Saudi citizens, and 52.09% were female. The majority (84.77%) said that the optimal period for vitamin D exposure in the sun is in the morning. In comparison, 54.32% said that exposed body areas, including the hands, arms, face, and legs, are necessary. Nearly 52% of respondents said their doctor had told them they were vitamin D deficient. Those who knew they had a shortage exhibited a favorable attitude towards taking vitamin D and adhered to their diet. Conclusion: By promoting appropriate and sane awareness among the populace, vitamin D deficiency can be avoided. Vitamin D understanding has grown over the past ten years in Saudi Arabia. To lessen vitamin D insufficiency in the Aseer region, however, the population's behaviour needs to be reinforced.